Restorasi ekologi lahan gambut berbasis kelompok masyarakat melalui revegetasi di Desa Tanjung Leban - Almasdi Syahza; Arifudin Arifudin; Osamu Kozan; Kei Mizuno; Michiko Hosobuchi; Hasrullah Hasrullah; Sunawiruddin Hadi; Asnawi Asnawi (Unri Conference Series: Community Engagement, 2020)
Ecological restoration of peatlands is an effort to restore damaged peatland ecosystems caused by human activities, whether intentional or not. Tanjung Leban Village is one of the villages with a large area of degraded peatlands and always experiences peat fires. The ecological restoration of peatlands in Tanjung Leban Village is an activity of the JICA Partnership Program (JPP), a collaboration between JICA, Kyoto University, and Riau University. The method of community empowerment is through village facilitators who are allocated in the village. The series of implementation processes began with socialization which was then continued with the emerging of the groups, seedling, land clearing, and planting. In particular, the implementation of revegetation activities focuses on community participants who are members of the Peat Care Community Group (MPG). This activity is carried out on community land, with an area of 28.4 Ha and 23,450 trees. These trees are divided into 2 categories, namely natural wood and fruit trees. Community empowerment activities change the community’s behaviour of peatland management in term of preventing peatland fires.